Factors Influencing the Growth of MSMEs and Their Impact on Employment Opportunities and Income Inequality in Java Island (2017–2019) - Arief Nugroho Wibowo; Heru Subiyantoro; Sugiyanto Sugiyanto; Pujiastuti Pujiastuti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study aims to analyze the factors influencing the growth of Micro, Small, and Medium Enterprises (MSMEs) and their impact on employment opportunities and income inequality in Java Island during the period 2017–2019. Using multiple linear regression analysis with SPSS software, the study examines the influence of seven independent variables: employment rate, Gini index, credit access, digitalization, infrastructure, education programs, and policy index on MSME growth as the dependent variable. The results reveal that the Gini index and education programs have a significant negative effect on MSME growth, while the policy index shows a significant positive effect. Other variables were found to be statistically insignificant, although high Variance Inflation Factor (VIF) values indicate potential multicollinearity. These findings suggest that income inequality and government policy effectiveness are critical determinants of MSME development. Policy implications emphasize the need for targeted interventions to reduce inequality, improve the relevance of entrepreneurship education, and maintain consistent regional policies to strengthen MSMEs' contributions to job creation and income equality in Indonesia.